Racial and gender wage differentials in South Africa: What can cohort data tell? - Carola Grün (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
High poverty rates as well as a very unequal distribution of income and wealth are distinctive features of post Apartheid South Africa. Studies analysing the extent of income inequality show that since the end of Apartheid the distribution of income has at best not changed at all, but depending on the measure, might also have worsened in the last decade. The data used in most of these studies are repeated cross sections, allowing a snapshot of the extent of income inequality at several points in time. Analysing temporal changes at an individual level is not possible. This paper proceeds differently. By using subsequent waves of the October Household Surveys and Labour Force Surveys a synthetic panel will be constructed. Preparing cross sectional data that way allows us to better utilise individual information and to address temporal developments also in the absence of genuine panel data. The paper focuses on gender and population group specific cohort wages to get a more detailed description of wage inequality. Average earnings of birth cohorts of African and White workers employed full-time in formal sector jobs are followed over time and wage differentials as well as the mobility of cohort wages are studied in detail. A decomposition of African cohort wages into age, cohort, and year effects gives information about the existence of cohort effects. Results suggest that especially for young African women such generational trends may differ from the theoretical expectation.
Keywords: D31; J31; 330; cohort data; wage differentials; generational trends